2018
DOI: 10.1177/1360780418754564
|View full text |Cite
|
Sign up to set email alerts
|

The Sociological Theory of Craftsmanship: An Empirical Test in Sport and Education

Abstract: The aim of this study is to test empirically the sociological theory of craftsmanship originally developed by C. Wright Mills, Torstein Veblen, and Howard Becker and later extended by Harper, Sennett, and Fine. We conduct a quantitative analysis based on a nationally representative sample of 10,783 Icelandic adolescents (50.2% girls). We developed a scale measuring craftsmanship that we use to test several hypotheses regarding the role of craftsmanship in sport and education. Our findings provide a consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…One promising avenue for understanding meaningful engagement in sport and movement culture practices is the theory of craftsmanship, which Sennett (2008, p. 9) described as "an enduring, basic impulse, the desire to do a job well for its own sake". Drawing on Sennett's book The Craftsman (2008) where craftsmanship is conceptualized as the "the special human condition of being engaged" (p. 20), scholars have argued that craftsmanship can be a key factor in understanding meaningful movement practices (Højbjerre Larsen, 2016; Thorlindsson et al, 2018). In addition to discussing the theoretical construct of craftsmanship and its relationship with sport, Thorlindsson et al (2018) also developed the first quantitative scale to assess craftsmanship and tested several hypotheses concerning the role of craftsmanship in schoolwork and youth sport in Icelandic adolescents.…”
Section: Beyond Health and Happiness: An Exploratory Study Into The Relationship Between Craftsmanship And Meaningfulness Of Sportmentioning
confidence: 99%
See 3 more Smart Citations
“…One promising avenue for understanding meaningful engagement in sport and movement culture practices is the theory of craftsmanship, which Sennett (2008, p. 9) described as "an enduring, basic impulse, the desire to do a job well for its own sake". Drawing on Sennett's book The Craftsman (2008) where craftsmanship is conceptualized as the "the special human condition of being engaged" (p. 20), scholars have argued that craftsmanship can be a key factor in understanding meaningful movement practices (Højbjerre Larsen, 2016; Thorlindsson et al, 2018). In addition to discussing the theoretical construct of craftsmanship and its relationship with sport, Thorlindsson et al (2018) also developed the first quantitative scale to assess craftsmanship and tested several hypotheses concerning the role of craftsmanship in schoolwork and youth sport in Icelandic adolescents.…”
Section: Beyond Health and Happiness: An Exploratory Study Into The Relationship Between Craftsmanship And Meaningfulness Of Sportmentioning
confidence: 99%
“…Drawing on Sennett's book The Craftsman (2008) where craftsmanship is conceptualized as the "the special human condition of being engaged" (p. 20), scholars have argued that craftsmanship can be a key factor in understanding meaningful movement practices (Højbjerre Larsen, 2016; Thorlindsson et al, 2018). In addition to discussing the theoretical construct of craftsmanship and its relationship with sport, Thorlindsson et al (2018) also developed the first quantitative scale to assess craftsmanship and tested several hypotheses concerning the role of craftsmanship in schoolwork and youth sport in Icelandic adolescents. They found that craftsmanship was negatively correlated with general and school-related meaninglessness; however, they did not assess craftsmanship in relation to positive indices of meaningful engagement or focus on meaningfulness specifically in the sport context and were focused specifically on adolescent participants.…”
Section: Beyond Health and Happiness: An Exploratory Study Into The Relationship Between Craftsmanship And Meaningfulness Of Sportmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of publications highlight that local, natural resource users, such as fishers, operate through different styles of work (Boonstra and Hentati-Sundberg 2016) that imply different kinds and qualities of knowledge and skill (Thorlindsson 1994;Lauer and Aswani 2009;King 2011). To distinguish the various degrees in which people mutually constitute practices with living and non-living nature and technical artifacts (Cooke, West, and Boonstra 2016) we theorize the distinctive qualities of ILEK with the concept of craftsmanship (Veblen 1914;Becker 1978;Harper 1987;Mills 1980Mills [1952Sennett 2008;Thorlindsson, Halldorsson, and Sigfusdottir 2018).…”
Section: Theorizing Indigenous and Local Ecological Knowledge Throughmentioning
confidence: 99%